Correlation of family expressed emotion and frequency of relapse schizophrenia patients - I Gusti Agung Ayu Putri Yuni Aryanti; Luh Nyoman Alit Aryani; Cokorda Bagus Jaya Lesmana (Indoscholar Publication and the Indonesian Psychiatric Association, 2020)
Background: Schizophrenia is a severe mental disorder in the psychiatric field, is chronic, and is characterized by recurring relapse. The causative factor that plays an important role is the expressed emotion (EE) of the family. The aim of this study was to determine the expressed emotion scores of families who treated schizophrenic patients at Sanglah Hospital.Methods: The study used a cross-sectional analytical method. Measurement of the EE of families using the Family Questionnaire (FQ). Data were analyzed descriptively and used the Spearman correlation test with a significance level of p <0.05.Results: The research participants were 61 families of schizophrenia patients treated at Sanglah Hospital, female (57.4%), and average age 45 years old. The results showed a correlation between the family’s expressed emotion score and the frequency of recurrence of schizophrenic patients in Sanglah Hospital, which was statistically significant (R=0.611, p <0.001). That value shows that the correlation between the family expressed emotion score and the frequency of relapse patients with schizophrenia at Sanglah Hospital has a strong categorical correlation.Conclusion: There is a significant correlation between the scores of family expressed emotion and the frequency of relapse in schizophrenia patients, where the expressed emotion of families is high, the frequency of relapse in schizophrenia patients will increase.